Perancangan Video Informasi Griya Glass - Suhudi, Kevin Dimas Achda; Wantoro, Wantoro (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
Stained glass is stained glass, made into a window of pieces on glass arranged to be images or patterns. Griya glass is one of the stained glass producers located in Bandung. Griya glass is having some troubles on production as there is no consistency in documentation of stained glass products, sticking phone number as their watermark and logo on photos puts the their reputation at risk, lack of detail on the product design style and the documentation quality of the products and the making process. Griya glass has social medias such as instagram and facebook, but the information about their products posted on same page as owner's personal life posts. Fluctuation of content consistency social media design sustain consumer’s confuse. In conclusion, update and post Griya Glass content, informations and products on social medias is necessary to decrease some of their problems. An information video is a fresh approach to inform everything happen and made by Griya Glass to their consumers. A video-based platform of information is mean spreading information about something important, to the audience, that intend to try to convince people about the products and Griya Glass itself so well.